Exam MS-100 Microsoft 365 identity and services. (Microsoft Press, 2023)
Over 2.5 Hours of Video Instruction to Help You Master Evaluating, Planning, Migrating, Deploying, and Managing Microsoft 365 to Pass Exam MS-100: Microsoft 365 Identity and Services. Exam MS-100 Microsoft 365 Identity and Services immerses you in the Microsoft 365 environment through detailed analysis coupled with hands-on demonstrations from seasoned Microsoft Certified Trainer Dan Costello. In this video course, you will learn the ins and outs of planning and deploying a Microsoft 365 tenant, including configuration of an organizational profile and subscription options, component services, user accounts and groups, and licensing. You will then learn how to set up monitoring of your new tenant, and strategically plan for migration of your existing users and their data. Security and Identity lie at the heart of every Microsoft cloud solution, so the course also includes an in-depth discussion of Azure Active Directory (Azure AD), including how to provision new directory objects, how to configure directory synchronization, and how to plan and implement secure authentication and authorization strategies. You will also determine how to plan for properly deploying a standard Microsoft 365 tenant to facilitate a successful migration to the cloud. Organized to comprehensively prepare you with the skills and knowledge to sit and pass Exam MS-100: Microsoft 365 Identity and Services, this video course also offers insight to enterprise administrators who are looking to expand their knowledge in Microsoft 365 workloads not currently in their purview. Learn How To: Design and implement Microsoft 365 services Manage user identity and roles Manage access and authentication Plan Office 365 workloads and applications Plan Microsoft Power Platform integration Who Should Take This Course? Individuals preparing to take Exam MS-100: Microsoft 365 Identity and Services Enterprise administrators planning to perform Microsoft 365 tenant-level planning, implementation, and administration of cloud and hybrid enterprise environments Course Requirements: Requires a basic knowledge of Microsoft 365 workloads and Microsoft Azure Active Directory (Azure AD). Viewers should also have a working knowledge of networking, server administration, DNS, and PowerShell. Lesson Descriptions: Lesson 1: Design and Implement Microsoft 365 Services This lesson focuses on best practices for the planning and design phases of rolling out a new Microsoft 365 deployment. These foundations pave the way for discussion and demonstrations of deploying a new Microsoft 365 tenant, including the basic process of setting up a tenant, doing some initial configuration, and getting support from a Microsoft partner. This sets the stage for covering some basic management topics, including setting up monitoring of your new tenant, and advancing to a strategic look at planning for migration of your existing users and their data. Lesson 2: Manage User Identity and Roles This lesson emphasizes how properly configured and managed Microsoft 365 user identities ensure that users can seamlessly access applications and services across your Microsoft 365 deployment. In turn, this attention to detail also eases the burden of administrators to manage fundamental elements such as product licensing, auditing, resource access, and role membership. This lesson provides you with the knowledge to make this a reality. Azure Active Directory is at the heart of your Microsoft cloud-based identity solution. As such, this lesson will also cover designing an identity strategy with attention to determining how your users should authenticate and whether you need to synchronize your cloud identity management solution with your on-premises solution. You'll also learn how to plan a synchronization strategy, including using the IdFix tool to review and prepare your on-prem Active Directory forest. This lesson also delves into developing a synchronization solution, using either Azure AD Connect (on-prem solution) or using Azure AD Connect cloud sync (a lightweight cloud-based alternative). Lesson 2 wraps up with a look at planning and managing Azure AD identities and groups, as well as granting granular administrative permissions to individual users and groups through Azure AD role management. Lesson 3: Manage Access and Authentication This lesson zeroes in on securing and managing access to Microsoft 365 applications and services by exploring additional security measures beyond those inherent with Azure Active Directory. This lesson explores multi factor authentication, setting up password management policies, and monitoring authentication events. You'll also learn how to deploy additional security measures in place to mitigate unusual or potentially risky user sign in behavior. This lesson wraps up with a look at how to use Azure AD to secure third-party and on-prem applications. Lesson 4: Plan Office 365 Workloads and Applications This lesson helps you plan for deployment of the standard Microsoft 365 apps by assessing existing on-prem assets to facilitate a successful migration to the cloud. This lesson also delves into a number of strategies for messaging deployments by migrating on-prem email solutions, either partially or fully, to Exchange Online and Outlook Online. You'll also learn how to plan for SharePoint online and OneDrive for business, including what's involved with migrating on premises file storage to a cloud-based solution. In addition, you'll learn to plan for capitalizing Teams infrastructure to optimize team management and voice communication. Finally, you'll explore planning Microsoft Power Platform integration and what's involved in preparing your organization for low code, no code development. About the Publisher Microsoft Press creates IT books and references for all skill levels across the range of Microsoft technologies: https://www.microsoftpressstore.com/ About Pearson Video Training Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Microsoft Press, Sams, and Que Topics include: IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.